Graduation guide for design students. - Paus, Moniek (Amsterdam : BIS, 2012)
This book is the perfect gift for all design students who embark on their most stressful year in design education: graduation year. This guide helps the student to graduate as a designer by giving practical advice, design advice and by suggesting ways to make graduation less stressful and more enjoyable. The advice is always very much on point and presented as double page spread posters with smart and funny illustrations and short handwritten text. You would want many of the spreads to hang on the door of your student room or studio.The dust jacket is a fold out poster that you can actually put on your wall. It is maybe the most important advice for the final exam student: Work Hard, Have Fun & Nooo Drama!
boek